2021
DOI: 10.3389/fcell.2021.665289
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Golgi Structural Proteins and Glycosylation Defects in Cancer

Abstract: As the central hub in the secretory and endocytic pathways, the Golgi apparatus continually receives the flow of cargos and serves as a major processing station in the cell. Due to its dynamic nature, a sophisticated and constantly remodeling mechanism needs to be set up to maintain the Golgi architecture and function in the non-stop trafficking of proteins and lipids. Abundant evidence has been accumulated that a well-organized Golgi structure is required for its proper functions, especially protein glycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 95 publications
0
40
0
Order By: Relevance
“…The centrality of the Golgi complex for many cellular and physiological functions has often attracted the attention of scientists to the role of this organelle in many areas of pathology, and in particular in the cancer field ( Liu et al, 2021 ; Zhang, 2021 ). The role of Golgi in cancer can be analyzed starting from its fundamental functions, for example protein transport and glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…The centrality of the Golgi complex for many cellular and physiological functions has often attracted the attention of scientists to the role of this organelle in many areas of pathology, and in particular in the cancer field ( Liu et al, 2021 ; Zhang, 2021 ). The role of Golgi in cancer can be analyzed starting from its fundamental functions, for example protein transport and glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that a proper Golgi structure is essential for its suitable functions, especially glycosylation (X. Zhang, 2021 ). Notably, altered glycosylation of cell surface proteins and lipids is a well-accepted cancer hallmark ( Martins et al, 2021 ; Zhang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Zhang, 2021 ). Notably, altered glycosylation of cell surface proteins and lipids is a well-accepted cancer hallmark ( Martins et al, 2021 ; Zhang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In tissue culture, the Golgi ribbon is intact in many cancer cell lines, but it undergoes morphological change upon the induction of epithelial-to-mesenchymal transition (EMT) or migration (Bisel et al, 2008b). Golgi fragmentation is often seen in various tumor tissue types from patients (Maldonado et al, 1966;Tani et al, 1975;Castejón, 1999;Kellokumpu et al, 2002;Sano et al, 2002;Zhang, 2021). Frozen tissue sections showed intact Golgi structure in normal colon epithelial cells, in contrast to small punctate Golgi structure found in cancerous colon epithelium FIGURE 1 | Golgi morphology in cancer cell lines.…”
Section: Golgi Fragmentation In Cancermentioning
confidence: 99%
“…While most cancer cell lines in culture have an intact Golgi ribbon, future research should investigate the Golgi structure in 3D models that better represent tumor microenvironment and cancer cell progression. Our speculation that Golgi alteration facilitates cancer biogenesis is based on the following reasons: 1) The Golgi undergoes morphological change in tissue culture upon the induction of EMT (Tan et al, 2017) or migration (Bisel et al, 2008b); 2) Golgi fragmentation is often seen in cancer tissues (Maldonado et al, 1966;Tani et al, 1975;Kellokumpu et al, 2002;Sano et al, 2002;Petrosyan, 2015;Zhang, 2021); 3) Alteration of Golgi functions such as glycosylation is a hallmark of cancer cells (Zhang, 2021). 4) While an organized Golgi structure is required for accurate protein glycosylation and sorting, our study revealed that Golgi fragmentation accelerates protein trafficking and cell proliferation (Xiang et al, 2013;Zhang and Wang, 2016;Bekier et al, 2017).…”
Section: Future Direction and Concluding Remarksmentioning
confidence: 99%